2023
DOI: 10.1093/dote/doad023
|View full text |Cite
|
Sign up to set email alerts
|

Maximum phonation time: an independent predictor of late-onset pneumonia after esophageal cancer surgery

Abstract: Dysphagia after esophagectomy is a major risk factor for aspiration pneumonia, thus preoperative assessment of swallowing function is important. The maximum phonation time (MPT) is a simple indicator of phonatory function and also correlates with muscle strength associated with swallowing. This study aimed to determine whether preoperative MPT can predict postoperative aspiration pneumonia. The study included 409 consecutive patients who underwent esophagectomy for esophageal cancer between 2017 and 2021. Pneu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…We found that MPT could serve as a predictor of PED, with a prevalence of 5.5% and 13.0% in the normal and abnormal MPT groups, respectively. This finding aligns with previous research identifying MPT as a predictive factor for postoperative complications—such as aspiration pneumonia 26 and dysphagia—in patients undergoing occipital spinal fusion. 27 We previously reported that even transient PED lowers functional status and worsens the long-term prognosis, strongly indicating the usefulness of the MPT.…”
Section: Discussionsupporting
confidence: 91%
“…We found that MPT could serve as a predictor of PED, with a prevalence of 5.5% and 13.0% in the normal and abnormal MPT groups, respectively. This finding aligns with previous research identifying MPT as a predictive factor for postoperative complications—such as aspiration pneumonia 26 and dysphagia—in patients undergoing occipital spinal fusion. 27 We previously reported that even transient PED lowers functional status and worsens the long-term prognosis, strongly indicating the usefulness of the MPT.…”
Section: Discussionsupporting
confidence: 91%